DESCRIPTIVE STUDY ON THE PERSONAL COMPUTER STATUS AS AN OBSERVER AND RECORDER-PARAMETER PROCESS PARAMETERS IN ELECTRICITY GENERATION - Sri Mulyaningsih; Djoko Hermanto., DR, MS. (Jurnal Sistem Informasi, 1990)
Advances in technology these days walking fast, along with the progress of information systemsthat cause this century referred to as the information age. In the industrial world, because bothare closely related.The power plant is one important component dalampenggunaan industry.In operation steam-Muara Karang, Jakarta has been to use the computer however there are stilldeficiencies in the way of determining the original cause of the abnormalities of a system in caseof trouble (error).For that they held a descriptive study of the personal computer as an observer and recorder statusparameters in the process of generating electricity by adding a bit of hardware on the existingsystem.The first goal of the desired results will be obtained that is able to determine the initial status of asystem abnormalities.